Nonlinear Speed Control of Switched Reluctance Motor Drives Taking into Account Mutual Inductance - M. Alrifai; M. Zribi; R. Krishnan; M. Rayan (Journal of Control Science and Engineering)
A speed control algorithm is proposed for variable speed switched reluctance motor (SRM) drives taking into account the effects of mutual inductances. The control scheme adopts two-phase excitation; exciting two adjacent phases can overcome the problems associated with single-phase excitation such as large torque ripple, increased acoustic noise, and rotor shaft fatigues. The effects of mutual coupling between two adjacent phases and their contribution to the generated electromagnetic torque are considered in the design of the proposed control scheme for the motor. The proposed controller guarantees the convergence of the currents and the rotor speed of the motor to their desired values. Simulation results are given to illustrate the developed theory; the simulation studies show that the proposed controller works well. Moreover, the simulation results indicate that the proposed controller is robust to changes in the parameters of the motor and to changes in the load torque.